Broadly Applicable Synthesis of Heteroarylated Dithieno[3,2-b:2′,3′-d]pyrroles for Advanced Organic Materials – Part 1: Conducting Electropolymers - Lorenz, Christoph; Vogt, Astrid; Millan, Judith; Mena-Osteritz, Elena; Bäuerle, Peter (Organic Materials, 2023)
Herein, a novel and versatile method for the synthesis of N-heteroarylated dithieno[3,2-b:2,3′-d]pyrroles (DTPs) is reported. By microwave-assisted Cu-catalyzed coupling of parent H-DTP 1 with 5- and 6-membered heteroaromatic halides, a variety of novel N-functionalized DTPs were obtained. Supported by quantum chemical calculations and X-ray structure analysis, structural and optoelectronic properties of the π-conjugated systems were investigated and led to valuable structure–property relationships. Selected derivatives were electropolymerized to corresponding conducting DTP polymers.
Keywords: organic materials; conjugated molecules; dithienopyrrole; Cu-catalyzed C – N coupling; optoelectronic properties; quantum chemical calculations; electropolymerization; poly(dithienopyrrole)